Digitalisation and productivity: Gamechanger or sideshow? - Bob Anderton; Vasco Botelho; Paul Reimers (European Central Bank (ECB), 2023)
Is digitalisation a massive gamechanger which will deliver huge gains in productivity, or is it more of a sideshow with only limited impacts? We use a large balance sheet panel dataset comprising more than 19 million European firm-level observations to empirically investigate the impact of digitalisation on productivity growth via various previously unexplored channels and mechanisms. Our results suggest that for two otherwise identical firms, the firm that exhibits on average a higher share of investment in digital technologies will exhibit a faster rate of TFP growth, but not all firms and sectors experience significant productivity gains from digitalisation. Digitalisation does not seem to have relatively stronger impacts on the productivity of frontier firms compared to laggards, nor does it help to turn laggards into frontier firms. Overall, firms should not regard digital investment as a 'one-size-fits-all' strategy to improve their productivity. Digital technologies are a gamechanger for some firms. But they seem more like a sideshow for most firms, who attempt to be increasingly digital but are not able to adequately reap its productivity gains.
Keywords: D22; D24; D25; O33; 330; digital technology/transition; productivity growth; technology adoption/diffusion